2011
DOI: 10.1159/000327913
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Levels of Triglyceride and Triglyceride-Rich Lipoprotein Triglyceride Induced by a High-Carbohydrate Diet Is Associated with Polymorphisms of <i>APOA5-</i>1131T>C and <i>APOC3-</i>482C>T in Chinese Healthy Young Adults

Abstract: Background/Aims: Changes in lipid profiles have been shown to be associated with diet and apolipoprotein (APO) polymorphisms. Therefore, 2 polymorphisms, i.e. APOA5-1131T>C and APOC3-482C>T, and serum lipids were examined in a Chinese healthy young population with high-carbohydrate/low-fat (HC/LF) diet intervention. Methods: After a wash-out diet for 7 days, 56 young adults (22.89 ± 1.80 years) received the HC/LF diet for 6 days. Body mass index (BMI) and fasting serum lipid profiles at baseline, after the was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 69 publications
(65 reference statements)
1
14
1
Order By: Relevance
“…After 12 weeks, however, -1131C allele carriers showed a significant increase in apoA-V concentrations, and the apoA-V levels of C allele carriers were no longer significantly different from those of TT allele carriers. This result contrasts the previous suggestion that increased triglyceride levels in individuals with the APOA5 -1131C allele after consumption of a high-carbohydrate and low-fat diet might possibly result from reducing the translational efficiency of apoA-V in the -1131C allele [13]. This contrasting result could be partly due to increased apoA-V production resulting from high triglyceride induced by a high carbohydrate diet with refined rice.…”
Section: Resultscontrasting
confidence: 92%
See 2 more Smart Citations
“…After 12 weeks, however, -1131C allele carriers showed a significant increase in apoA-V concentrations, and the apoA-V levels of C allele carriers were no longer significantly different from those of TT allele carriers. This result contrasts the previous suggestion that increased triglyceride levels in individuals with the APOA5 -1131C allele after consumption of a high-carbohydrate and low-fat diet might possibly result from reducing the translational efficiency of apoA-V in the -1131C allele [13]. This contrasting result could be partly due to increased apoA-V production resulting from high triglyceride induced by a high carbohydrate diet with refined rice.…”
Section: Resultscontrasting
confidence: 92%
“…The increase in triglyceride in control subjects with the C allele is in agreement with the previous study that APOA5 -1131C-allele carriers had higher triglyceride concentrations in response to a high-carbohydrate and low-fat diet (70 and 15% of energy derived from carbohydrate and fat, respectively) in young, healthy, Chinese adults [13]. However, the reduction of triglyceride concentrations by a 9-week low-calorie and low-fat (52 and 30% of energy derived from carbohydrate and fat, respectively) intervention was not associated with the APOA5 -1131 T > C in overweight and obese nondiabetic Czech females [27].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…We did not find any triglyceride difference in all groups examined. High triglyceride levels associated with the APOC3 variant have been observed in obese men [28] and as consequence of a specific diet (high carbohydrate, [29]) often in oriental populations. Furthermore, APOC3 polymorphisms have been correlated with altered postprandial lipid metabolism [30].…”
Section: Discussionmentioning
confidence: 99%
“…Previous observational studies and intervention trials have shown that the APOA5 -1131 T > C polymorphism interacts with dietary factors, especially dietary fat, to determine triglyceride concentrations [10-14]. Lin et al recently showed that elevated triglyceride levels were induced by a high carbohydrate diet in healthy individuals with the APOA5 -1131C allele [15]. A clear association exists between diabetic dyslipidemia and the APOA5 -1131 T > C polymorphism [16].…”
Section: Introductionmentioning
confidence: 99%